Regulatory Colonialism in Global Sports Competitions: Legal Implications for Athletes from Developing Countries - Gevan Naufal Wala (Siber Nusantara Review, 2024)
This research examines the phenomenon of regulatory colonialism in global sports governance and its legal implications for athletes from developing countries. Through socio-legal analysis and a postcolonial theoretical framework, this study investigates the historical formation of international sports organizations, the Eurocentric values embedded in competition standards, and the structural inequalities perpetuated through current regulatory systems. The research reveals significant disparities in qualification policies, anti-doping regulations, infrastructure requirements, and athlete transfer rules that disadvantage developing nations. Furthermore, athletes from these countries face substantial procedural and financial barriers to accessing justice in international sports disputes. This study identifies concrete manifestations of regulatory colonialism in contemporary sports, including inequitable resource distribution, exploitative commercial arrangements, and inadequate representation in decision-making processes. The research concludes by proposing legal reforms centered on equitable representation, resource redistribution, cultural diversity recognition, and strengthened justice access mechanisms to decolonize global sports governance and advance structural equality.